Long-Term Dietary Nitrate Supplementation Does Not Prevent Development of the Metabolic Syndrome in Mice Fed a High-Fat Diet - V. B. Matthews; R. Hollingshead; H. Koch; K. D. Croft; N. C. Ward (International Journal of Endocrinology)
Background. Nitric oxide (NO) is an important vascular signaling molecule that plays a role in vascular homeostasis. A reduction in NO bioavailability is thought to contribute to endothelial dysfunction, an early risk factor for both cardiovascular disease and type 2 diabetes. Dietary nitrate, through the nitrate-nitrite-NO pathway, may provide an alternate source of NO when the endogenous eNOS system is compromised. In addition to a role in the vascular system, NO may also play a role in the metabolic syndrome including obesity and glucose tolerance. Aim. To investigate the effect of long-term dietary nitrate supplementation on development of the metabolic syndrome in mice fed a high-fat diet. Methods. Following 1 week of acclimatisation, male (6–8 weeks) C57BL6 mice were randomly assigned to the following groups (10/group) for 12 weeks: (i) normal chow + NaCl (1 mmol/kg/day), (ii) normal chow + NaNO3 (1 mmol/kg/day), (iii) high-fat diet + NaCl (1 mmol/kg/day), and (iv) high-fat diet + NaNO3 (1 mmol/kg/day). Body weight and food consumption were monitored weekly. A subset of mice (5/group) underwent running wheel assessment. At the end of the treatment period, all mice underwent fasting glucose tolerance testing. Caecum contents, serum, and tissues (liver, skeletal muscle, white and brown adipose, and kidney) were collected, frozen, and stored at −80°C until analysis. Results. Consumption of the high-fat diet resulted in significantly greater weight gain that was not affected by dietary nitrate. Mice on the high-fat diet also had impaired glucose tolerance that was not affected by dietary nitrate. There was no difference in adipose tissue expression of thermogenic proteins or energy expenditure as assessed by the running wheel activity. Mice on the high-fat diet and those receiving dietary nitrate had reduced caecum concentrations of both butyrate and propionate. Conclusions. Dietary nitrate does not prevent development of the metabolic syndrome in mice fed a high-fat diet. This may be due, in part due, to reductions in the concentration of important short-chain fatty acids.